Sistem Penggajian Badan Pusat Statistik Kabupaten Nabire Berdasarkan Absensi - Irma Rosdiana; Ester Ayuk Pusvita; Arief Rahman Hakim (STMIK Pesat Nabire, 2023)
The sophistication of current technology is evident in our daily lives. In Indonesia, the government supports digital-based programs aimed at modernizing life and improving the well-being of society. Conventional systems are transitioning to more efficient digital systems. A system, a collection of components working together to achieve specific tasks, is crucial; one such example is the attendance system. During an internship at the Nabire Regency Central Bureau of Statistics (BPS), opportunities were observed to develop an application to streamline existing processes. The proposed web-based payroll application would calculate employee salaries based on attendance, enhancing the efficiency and organization of payroll and attendance systems at the Nabire Regency BPS.